Earmarked Paternity Leave and Well-Being - Pontus Korsgren; Max van Lent (Institute of Labor Economics (IZA), 2022)
Earmarked paternity leave has been introduced in an attempt to increase fathers' involvement in child rearing and to achieve gender equality in the labor market and at home. So far well-being effects of such policies are unexplored. This paper takes a first step in that direction by studying the impact of earmarked paternity leave quota on life satisfaction, job satisfaction, and work-life balance using several policy changes in Europe over the period 1993-2007. We find that earmarked paternity leave increases life satisfaction by 0.18 on a 10 point scale which is equivalent to a 10.8 percentage point increase even decades later. Both fathers and mothers benefit, though the increase in life satisfaction for mothers is nearly 30% higher than that of fathers. Perhaps surprisingly, the impact on job satisfaction and work-life balance is close to zero. Hence even when the impact of paternity leave quota on the labor market are small, the increases in life satisfaction may still justify the existence of such policies.
Keywords: J12; J13; J16; J18; I31; I38; 330; family leave policies; paternity leave; quota; well-being; life satisfaction